Penerapan Model Pembelajaran Kooperatif Tipe STAD Berbantuan Media Flip Chart Dilengkapi LKS Tebak Gambar Untuk Meningkatkan Hasil Belajar Siswa : (Implementation of The STAD Type Cooperative Learning Model Using Flip Chart Media Completed With The Picture Guessing LKS to Improve The Learning Outcomes of Grade) - Ambu, Soviati Ata; Bano, Vidriana Oktoviana; Tamaela, Kevin Andrean (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
This research is motivated by the low learning outcomes and activities of grade XII-IPA students at SMA Muhammadiyah Waingapu on Biotechnology material. The main problems include low literacy, lack of focus, and learning methods that are not yet varied. This Classroom Action Research (CAR) aims to improve cognitive and affective learning outcomes through the Student Teams Achievement Division (STAD) cooperative model assisted by Flip chart media and LKS Tebak Gambar (Guess the Picture) worksheets. The research subjects consisted of 26 students. Data were collected through tests (post-test), observation, and documentation, then analyzed quantitatively descriptively. The results showed a significant increase in each cycle. The average cognitive score increased from 59.61 (Pre-cycle) to 74.23 (Cycle I), and reached 86.15 (Cycle II) with a classical completeness of 88%. The affective aspect also increased, marked by the dominance of the